The Effect Of Information Asymmetry, Company Size And Managerial Ownership On Income Management (Empirical Study on Manufacturing Companies Listed on the Indonesia Stock Exchange) - Farid Addy Sumantri; Agus Kusnawan; Rr. Dian Anggraeni (Primanomics : Jurnal Ekonomi & Bisnis, 2021)
Earnings Management is the action of a manager by presenting reports that increase or decrease profit for the current period of the business unit for which is responsible, without causing an increase or decrease in the unit's long-term economic profitability. The purpose of this study was to examine the effect of information asymmetry, Company Size and Management ownership of Earnings Management in various industry sector companies listed on the Indonesia Stock Exchange 2017-2019. The sample used in this study consisted of 93 samples of various industrial, basic and chemical sector companies listed on the Indonesia Stock Exchange during the 2017- 2019 periods. The sample was selected using purposive sampling method. Earnings management is proxied by Discretionary Accrual using the Modified Jones Model. The data analysis method used in this research is multiple linear regression analysis. The results showed that information asymmetry has an effect on earnings management, firm size has no effect on earnings management, and management ownership has no effect on earnings management. The results of this study also prove that simultaneously information asymmetry, firm size and managerial ownership have an effect on earnings management